Emerging Themes in Epidemiology - Tam, Clarence
Emerging Themes in Epidemiology aims to promote debate and discussion on practical and theoretical aspects of epidemiology. We welcome primary research and discursive articles. We particularly encourage submissions in the following areas: New epidemiological concepts and methods, including new statistical methods Novel ways of presenting and providing insights into existing epidemiological concepts and methods, including in a teaching environment Use of epidemiological research methods in non-medical settings Causal inference in epidemiology Applications of new technologies in field studies Ethical issues in epidemiological research Methodological developments in molecular and genetic epidemiology and novel applications in these areas Historical articles and re-assessments of classic papers.